2015
DOI: 10.15845/jper.v2i2.817
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to participation in vocational orientation programmes among prisoners

Abstract: This study investigates the barriers to prisoners' participation in vocational orientation programmes, as well as the predictors of different types of barriers. Survey data derived from a project in a remand prison in Belgium (N=468) provided the empirical evidence for the analyses. The results indicate that facing situational and informational barriers are most common. Based on the different kinds of barriers, various types of non-participants can be distinguished and multinomial logistic regression analyses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 22 publications
2
13
0
Order By: Relevance
“…We consider prison call and visit as pull factors because families could drive inmates into education programs through constant encouragement, care, and comfort. As mentioned earlier, inmates with frequent contacts with the outside world tend to be associated with greater participation in prison education (Brosens et al, 2015; Velasquez, 2016). In fact, the mere presence of family members, even just their voice, could remind inmates of their current status and future responsibilities, and, thus, may work as incentives for inmates’ participation in correctional education.…”
Section: The Current Studymentioning
confidence: 92%
See 3 more Smart Citations
“…We consider prison call and visit as pull factors because families could drive inmates into education programs through constant encouragement, care, and comfort. As mentioned earlier, inmates with frequent contacts with the outside world tend to be associated with greater participation in prison education (Brosens et al, 2015; Velasquez, 2016). In fact, the mere presence of family members, even just their voice, could remind inmates of their current status and future responsibilities, and, thus, may work as incentives for inmates’ participation in correctional education.…”
Section: The Current Studymentioning
confidence: 92%
“…The push–pull perspective is most explicitly developed in the sociology of education to explain individuals’ motivations and decisions in education (see Elster, 1979; Gambetta, 1987). This perspective has been adopted by researchers of prisoner rehabilitation to further our knowledge on reasons behind inmates’ participation in rehabilitation programs or the barriers thereof (e.g., Brosens, De Donder, Dury, & Verté, 2015; Brosens, De Donder, Dury, & Verté, 2016; Costelloe, 2003; Eikeland, 2009; Manger, Eikeland, & Asbjørnsen, 2013; Manger et al, 2010).…”
Section: Prior Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…Several other studies have shown an increased prevalence of learning challenges with implications for education and academic training [4][5][6]9,[18][19][20][21]. Several studies have suggested that education affects recidivism and reintegration in the community following release [22][23][24][25][26], but several barriers to participation have also been reported [27][28][29] The reviewed data show that prison education programs constitute important arenas for adult education and adult education counselling. A relatively high proportion of prisoners in Norway choose to participate in education and training as part of the sentencing [30], and correctional services are important arenas for adult education.…”
Section: Introductionmentioning
confidence: 99%